Um estudo sobre a percepção do cliente pré-pago quanto ao serviço de roaming de chamadas terminadas - Nunes, Márcio Mendonça (2001)
The Cellular Service in Brazil has changed dramatically during the last few years in terms oftechnology innovation and the services offered to the marketplace. The regulatory environment evolved from a State monopoly to a regional duopoly that is current1y in place. The introduction of competition, resulted in benefits to the clients such as price reduction in acquisition and tariffs, not to mention the increase in the offer of cellular serVlces. In 1999 the Pre paid Service was introduced in Brazil with a great success. The service is suitable for clients who want to control their cellular expenses and also allowed clients from classes C and D to have access to cellular services. When the service was launched there was a limitation that didn't allow the user to roam outside the concession area of the carrier. The technical problem was solved months after launch and different service operators in Brazil adopted different marketing strategies. Some of them offered the roaming feature to alI their pre paid client base. Others segmented the market creating two pre paid products. Americel, cellular operator of a large Brazilian region, composed of the Federal District and the States of Goiás, Mato Grosso, Mato Groso do Sul, Tocantins, Rondônia and Acre, decided to segment the pre paid market and to offer two products: one with the roaming capability in the whole country and other without the roaming capability. The products have other differences and also their own tariff plano The purpose ofthis research is to evaluate how Americel's pre paid clients perceive the roaming feature for terminated calIs. The research intends to evaluate how important is roaming for the clients, how the client perceive the roaming provided by Americel and how the client classify the roaming feature as being a basic factor, a performance factor or an excitement factor of the cellular service. From the understanding of the client perception related to the roaming capability, the marketing strategy will be reevaluated The methodology employed is based in tools used to measure customer satisfaction. Americel performs a monthly customer satisfaction survey with a sample of 400 clients who are interviewed by phone. Each customer answers 50 questions about several aspects VIII related to the acquisition and the use ofthe service. Previous results appointed coverage as the most important feature of cellular services from a customer point ofview. The research also shows a misunderstanding about roaming and coverage. Customers tend to consider both attributes as the same thing. When they are asked about places where they need coverage their answers pointed out regions where Americel is not allowed to cover according to regulation. Inside these places Americel offers roaming. Roaming related questions were added to the original questionnaire to evaluate the frequency of traveI, the importance assigned to roaming, the evaluation of Americel's roaming service and the general evaluation of Americel. The results showed that roaming is important or very important to a large amount of clients. Americel's evaluation related to roaming is not good, what indicates that actions should be taken in order to improve the roaming capability for pre paid clients. Penalty-reward analysis results showed that roaming is considered as a performance factor of the cellular service. It means that when roaming is not achieved it creates dissatisfaction, but when it is achieved or exceeded it creates customer satisfaction. So, once more, is confirmed the need to offer roaming for terminated calls for all pre paid client base. Therefore, the conclusion is that the marketing strategy used by Americel to segment the pre paid market causes dissatisfaction to a large amount of clients and should be reviewed by the company.